2015
DOI: 10.1039/c5ta03193a
|View full text |Cite
|
Sign up to set email alerts
|

Layered ternary sulfide CuSbS2 nanoplates for flexible solid-state supercapacitors

Abstract: Layer-structured materials are advantageous for supercapacitor applications owing to their ability to host a variety of atoms or ions, large ionic conductivity and high surface area. In particular, ternary or higher-order layered materials provide a unique opportunity to develop stable supercapacitor devices with high specific capacitance values by offering additional redox sites combined with the flexibility of tuning the interlayer distance by substitution. CuSbS 2 is a ternary layered sulfide material that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 52 publications
4
56
0
Order By: Relevance
“…Among these CuSbS2 is particularly interesting, but less explored material. Recent studies show that an indium-free CuSbS2 is a promising p-type material for solar cell and supercapacitor applications [10][11][12][13][14][15] . Yang et al 12 confirmed the ptype conductivity theoretically and experimentally by using density functional theory calculations and Hall effect measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Among these CuSbS2 is particularly interesting, but less explored material. Recent studies show that an indium-free CuSbS2 is a promising p-type material for solar cell and supercapacitor applications [10][11][12][13][14][15] . Yang et al 12 confirmed the ptype conductivity theoretically and experimentally by using density functional theory calculations and Hall effect measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the electron propagation mechanism in Bi 2 S 3 micro-and nanospheres is expected to be more random, i.e., without a preferential direction, resulting in insufficient utilization of the electroactive sites for redox reactions at high current densities. Ramasamy et al [52] also confirmed the advantage of a nanoplate-like morphology over other morphologies for supercapacitor applications and indicated that a layered nanoplate structure ensures effective insertion and extraction of electrolyte ions.…”
Section: Electrochemical Measurements Of Bi 2 Smentioning
confidence: 60%
“…In contrast, low-temperature and energy-saving solution-based methods have been demonstrated to be very powerful to obtain desired MMSs. In this regard, many solution-based synthesis methods including coprecipitation, [29,48] hot injection, [49][50][51][52][53][54] refluxing, [55][56][57][58][59] hydro/ solvothermal, [60][61][62][63][64] electrodeposition, [65][66][67][68][69] and self-template methods [27,28,31,32] have been well established to synthesize high-quality MMSs.…”
Section: Brief Overview Of Synthesis Methods For Mmssmentioning
confidence: 99%
“…However, similar to LIBs, the cycling performance of CuSbS 2 for SIBs is also very poor. [52] Copyright 2015, Royal Society of Chemistry. Panels (c-e): Reproduced with permission.…”
Section: Libs/sibsmentioning
confidence: 99%
See 1 more Smart Citation